Fabrication and microstructure of a new ternary solid solution of Ti3Al0.8Si0.2Sn0.2C2 with high solid solution strengthening effect. Issue 8 (1st June 2018) - Cai, Leping; Huang, Zhenying; Hu, Wenqiang; Lei, Cong; Wo, Shaoshuai; Li, Xinkang; Zhai, Hongxiang; Zhou, Yang
Abstract: Nearly pure Ti3 Al0.8 Si0.2 Sn0.2 C2 solid solution powders were synthesized using the Ti, Al, Si, Sn and TiC powders as raw materials by pressureless sintering at 1450 °C for 10 min in Ar atmosphere. The Ti3 Al0.8 Si0.2 Sn0.2 C2 grains have a typical lamellar structure of MAX phase and the A-site elements of Al, Si and Sn are uniformly distributed in Ti3 Al0.8 Si0.2 Sn0.2 C2 grains through Energy Dispersive X-ray Spectrometer (EDXS) analysis. Almost fully dense Ti3 Al0.8 Si0.2 Sn0.2 C2 bulk was prepared using a two-time hot-pressing method at 1450 °C for 30 min under a pressure of 30 MPa. Both Rietveld refinement and High Resolution Transmission Electron Microscopy (HRTEM) confirmed the formation of the Ti3 Al0.8 Si0.2 Sn0.2 C2 solid solution and distortion of the crystal structure. The flexural strength and Vickers hardness of Ti3 Al0.8 Si0.2 Sn0.2 C2 were measured to be 649 ± 27 MPa and 6.4 ± 0.12 GPa (under a load of 4.9 N), respectively, higher than those of single phase Ti3 AlC2 or Ti3 AlSn0.2 C2 and Ti3 AlSi0.2 C2 solid solutions, indicating a solid solution strengthening effect. Grain delamination and kink bands formation can be extensively observed on the indentation area and fracture surface.